Canon law aspects of children’s rights - Anzelm Szuromi, Szabolcs (European Integration Studies, 2023)
The canonical system of the Catholic Church considers the human being as a person who, according to the revelation, is created in the image and likeness of God and therefore deserves equal human dignity (regardless of age, gender; biological-, physical-, spiritual-, social conditions). This explains the fact that canon law sources already before a separate “children’s rights system” (i.e., 20th century) protected children’s rights from the time of the Early Church. Naturally, there is the painful phenomenon of sexual abuse of minors, which has been the most highlighted issue in the Church’s relationship with children in the last decades. It might seem that the protection of the rights of minors (i.e., children) is limited to the prevention and sanctioning of this gravest delict and the special care of the victims. However, the protection of children’s rights within the Church is much broader. Therefore, the right of parents to educate their children freely following their faith is also an essential right according the Church’s documents, since 1929.